Pre-Existing Immunity with High Neutralizing Activity to 2009 Pandemic H1N1 Influenza Virus in Shanghai Population - Liu, Xiaoqing; Liu, Yuan; Zhang, Yanjun; Chen, Zhihui; Tang, Ziwei; Xu, Qingqiang; Wang, Yue; Zhao, Ping; Qi, Zhongtian (PloS one, 2013)
Pre-existing immunity is an important factor countering the pandemic potential of an emerging influenza virus strain. Thus, studying of pre-existing immunity to the 2009 pandemic H1N1 virus (2009 H1N1) will advance our understanding of the pathogenesis and epidemiology of this emerging pathogen. In the present study, sera were collected from 486 individuals in a hospital in Shanghai, China, before the 2009 H1N1 influenza pandemic. The serum anti-hemagglutinins (HA) antibody, hemagglutination inhibition (HI) antibody and neutralizing antibody against the 2009 H1N1 were assayed. Among this population, 84.2%, 14.61% and 26.5% subjects possessed anti-HA antibody, HI antibody and neutralizing antibody, respectively. Although neutralizing antibody only existed in those sera with detectable anti-HA antibody, there was no obvious correlation between the titers of anti-HA and neutralizing antibody. However, the titers of anti-HA and neutralizing antibody against seasonal H1N1 virus were highly correlated. In the same population, there was no correlation between titers of neutralizing antibody against 2009 H1N1 and seasonal H1N1. DNA immunization performed on mice demonstrated that antibodies to the HA of 2009 pandemic and seasonal H1N1 influenza viruses were strain-specific and had no cross-neutralizing activity. In addition, the predicted conserved epitope in the HA of 2009 H1N1 and recently circulating seasonal H1N1 virus, GLFGAIAGFIE, was not an immunologically valid B-cell epitope. The data in this report are valuable for advancing our understanding of 2009 H1N1 influenza virus infection.